2022
DOI: 10.5551/jat.59857
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Large Artery Atherosclerosis could Reveal Small Artery Retinopathy in Untreated Middle-Aged Individuals

Abstract: Small arteries can be visualized in the ocular fundus, and findings of retinopathy based on Scheie classification are often applied to evaluate the impact of hypertension and atherosclerosis. However, the relationship between damage in the large and small arteries has not been investigated sufficiently, especially in the early stages. The present study investigated possible associations between large artery atherosclerosis and small artery retinopathy in untreated middle-aged individuals. Methods: Untreated mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…3 Epidemiology evidence also showed that large artery AS indicates small artery retinopathy in untreated middle-aged individuals and vice versa. 4 As demonstrated by our study, ASTE administration reduced AS-lesions in the aortic arch, thoracic aorta plaques, and the retinal fundus vascular. However, some studies concluded that supplementation with ASTE did not prevent atherogenesis or aortic damage in AS rabbits.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…3 Epidemiology evidence also showed that large artery AS indicates small artery retinopathy in untreated middle-aged individuals and vice versa. 4 As demonstrated by our study, ASTE administration reduced AS-lesions in the aortic arch, thoracic aorta plaques, and the retinal fundus vascular. However, some studies concluded that supplementation with ASTE did not prevent atherogenesis or aortic damage in AS rabbits.…”
Section: Discussionsupporting
confidence: 71%
“…Moreover, microvascular disease, especially retinopathy, has been indicated as the most crucial complication of AS. 3,4 Traditionally, statin-based drugs were permitted to treat AS. 5 However, many of these are along with side effects, such as heart diseases and body immunity disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Atherosclerosis (AS) is a leading cause of coronary heart disease. [1][2][3][4] Vascular endothelial cells (VECs) are a major cell type that reside in the arterial walls, and aberrant behaviors of VECs may contribute to the development of AS. 5 A previous study found that excessive reactive oxygen species (ROS) produced as a result of external stimulation leads to oxidative stress injury, which is the main cause of endothelial dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…1) 2,5) , and the findings of the Sugiura's study were consistent with this concept. Moreover, Sugiura et al found a close association of IMT (representing morphological vascular damage), rather than CAVI (representing functional vascular damage), with retinopathy 4) , and these findings suggest that the direct effect of risk factors on cardiovascular disease, rather than pulsatile microvasculopathy, is a major player for morphological microvascular damages in the early stages of atherosclerosis. However, in the pulsatile microvasculopathy, blood pressure itself is one of the major players 2,5) , and pulse wave velocity (PWV), which is a marker of functional vascular damage in macrocirculation, rather than blood pressure adjusted PWV, had a close association with the progression of retinopathy 6) .…”
mentioning
confidence: 98%
“…In this issue, Sugiura et al examined the crosssectional associations of morphological/functional vascular damages in macrocirculation, which was assessed by the measurements of carotid intima-media thickness (IMT) and cardio-ankle vascular index (CAVI), with morphological vascular damages in microcirculation, which was assessed by the presence and extent of retinopathy, in subjects without the manifestations of atherosclerotic vascular damages 4) . They found a cross-sectional association of both morphological/functional vascular damages in macrocirculation with morphological vascular damages in microcirculation 4) .…”
mentioning
confidence: 99%